Transcatheter aortic valve implantation in degenerated trans-catheter and surgical bioprosthetic aortic valve. (14th October 2021) - Chanchai, R; Ancona, M R; Ancona, M; Montorfano, M
Abstract: Background: The moving forward indication of transcatheter aortic valve implantation (TAVI) to younger aortic valve stenosis (AS) patients might lead to degenerated trans-catheter heart valve (TAV) issues which need re-intervention. TAVI in a degenerated bioprosthetic surgical valve (SAV) is feasible. However, the results of TAVI-in-TAV when compare to TAVI-in-SAV have been rarely reported. Purpose: The aims of this study is to compare device success, early safety events at 30 days, clinical efficacy events after 30 days, and time related valve safety events between TAVI-in-TAV and TAVI-in-SAV. Methods: Retrospectively analysed data from 62 consecutive patients with degenerated TAV or SAV who received TAVI at our Scientific institute from January 2016 to June 2020. Results: 10 patients who received TAVI-in-TAV and 52 patients who received TAVI-in-SAV were included. The patient median age was 78 years and 60% was male. The median STS score was significantly higher in TAVI-in-TAV compared to TAVI-in-SAV groups; 7.80% vs. 3.30% respectively, p=0.006. The age of the first bioprosthetic was longer in TAVI-in-SAV compared to TAV-in-SAV group; 9.8 versus 5.3 years, respectively. All TAVI devices used in both groups were second generation. The device success rate, early safety at 30 days, clinical efficacy events at median 2-years follow up were comparable; 90% vs. 88.5%, 80% vs. 76.9%, 70% vs. 44.2%, in TAVI-in-TAV and TAVI-in-SAV groups respectively. All-cause mortality at 2-years follow up was comparable; 10% vs. 9.8% in TAVI-in-SAV and TAVI-in-SAV groups, respectively. Time related valve safety events at 2-years follow up was comparable; 30% vs. 26.9% in TAVI-in-TAV and TAVI-in-SAV groups respectively. Most valve safety events were related to residual high trans-aortic valve gradient which found only in small first bioprosthetic valve. The rate of new permanent pacemaker implantation was 16.7% in both groups. The coronary obstruction found was 19.2% in TAVI-in-SAV group. Conclusions: TAVI-in-TAV is feasible and comparable on device success, immediate and 2-years follow up outcomes compared to TAVI-in-SAV. Larger studies with longer-term follow-up time are needed to confirm these results as well as the upstream management of AS patient with long life expectancy. FUNDunding Acknowledgement: Type of funding sources: None.